HIGH RESOLUTION IMAGING IN THE INHOMOGENEOUS CRUST WITH COSMIC-RAY MUON RADIOGRAPHY: THE DENSITY STRUCTURE BELOW THE VOLCANIC CRATER FLOOR OF MT. ASAMA, JAPAN - Tanaka H.K.M.; Takeo M.; Oikawa J.; Ohminato T.; Aoki Y.; Koyama E.; Tsuji H.; Nakano T.; Takahashi S.; Yoshida J.; Niwa K. (My University, 2007)
We have developed a novel radiographic imaging method to survey the inhomogeneous structure of the crust. As an example, we performed measurements at Mt. Asama volcano, and studied the feasibility of using an azimuthally isotropic flux of cosmic-ray muons in the energy range up to a few TeV. The principle of the technique is that by measuring muon absorption along different nearly horizontal paths through a solid body, one can deduce the density distribution in the interior of the object. A muon detector with an area of 4000 cm2 was installed in a 1-m deep instrument vault located about 1 km from the summit crater of Mt. Asama. Muon tracks within emulsion layers in the detector were analyzed by 3d image processing to determine the level of energy absorption along different ray paths through the summit crater region. A typical angular resolution of the muon detector of 10 milliradians (mrad) corresponds to a spatial resolution of 10 m at a distance of 1 km. The measurements would be ideal for studying the shallow structure of the crust at sites which cannot be well resolved because of their strong structural heterogeneity and potential difficulty to be accessed, and which therefore cannot have their structure determined by conventional electromagnetic or seismic techniques. The present method can also provide three dimensional images of the subsurface by making measurements from two or more different points. In this work, we have radiographically imaged a few hundred meters below the crater floor of Mt. Asama, Japan, and have detected a dense region, which corresponds to the position and shape of a lava mound created during the last eruption (Urabe, B., Watanabe, N., Murakami, M., Topographic change of the summit crater of Asama Volcano during the 2004 eruption derived from Airborne Synthetic Aperture Radar (SAR) measurements, Bulletin of Geographical Survey Institute, 53, 1-6 (2006).). Right below the lava mound we found a low density region that suggests a drain-back-induced porous conduit (Urabe, B., Watanabe, N., Murakami, M., Topographic change of the summit crater of Asama Volcano during the 2004 eruption derived from Airborne Synthetic Aperture Radar (SAR) measurements, Bulletin of Geographical Survey Institute, 53, 1-6 (2006).). The density contrast was resolved with a precision of 1-3%. This method provides a resolution of the shallow density structure that is significantly higher than is possible with conventional geophysical measurements. © 2007 Elsevier B.V. All rights reserved.
Keywords: COSMIC-RAY MUON; EMULSION CLOUD CHAMBER; RADIOGRAPHY; VOLCANO; VULCANIAN ERUPTION